2018
DOI: 10.1177/0218492318778485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iodopovidone versus bleomycin in chemical pleurodesis

Abstract: Background Malignant pleural effusion continues to be a common problem in patients with metastatic disease. This study was conducted to compare the efficacy and safety of bleomycin pleurodesis with povidone-iodine pleurodesis through a chest drain as palliative treatment for recurrent malignant pleural effusion. Methods Sixty cancer patients (36 males and 24 females) with recurrent malignant pleural effusion were enrolled in a prospective randomized trial. Thirty patients received povidone-iodine pleurodesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
“…[ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 38 55 ] Kerman,[ 45 53 ] Tabriz,[ 16 36 ] Mashhad,[ 18 19 ] Yasouj,[ 44 ] Gorgan,[ 49 ] Neyshabour,[ 50 ] Jiroft,[ 46 47 ] Meybod/Ardakan,[ 54 ] Gorgan/Gonabad. [ 23 ] Majority of studies had quantitative approach, including interventional,[ 17 18 19 22 23 29 31 33 35 44 47 49 54 ] descriptive,[ 20 39 41 42 50 53 ] and correlational-analytical. [ 37 45 46 51 ] This was then followed by qualitative[ 12…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuando la LK se localizada a nivel torácico, se puede considerar la indicación de un acceso quirúrgico (idealmente por videotoracoscopía), especialmente si existen síntomas de ocupación pleural (Luisi et al;Ozeki et al, 2019a). Para reducir el derrame pleural recurrente, esta indicado la pleurectomía parietal, ligadura del conducto torácico o la pleurodesis con 15 a 120 U de bleomicina intracavitario diluida en 100 cc de solusión salina y removida 6 a 24 horas después (Bagheri et al, 2018).…”
Section: Discussionunclassified
“…In these studies, it was highlighted that the incidence of chest pain after CP was as high as 55% and 31% respectively, and attention should be paid to possible allergic reactions, cardiopulmonary insufficiency, thyrotoxicosis, nephrotoxicity, and visual impairment. However, other studies have shown that the above adverse reactions are usually rare, as long as the dosage, concentration, and time of PI are well controlled to avoid excessive absorption by the pleura during the treatment process (18).…”
Section: A B Cmentioning
confidence: 99%